Programovatelný atenuátor pro laboratorní měření - Husslik, Tomáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2024)
Práce se zabývá návrhem programovatelného atenuátoru s digitálním řízením. Cílem práce je návrh atenuátoru s impedancí 50 s útlumem v rozsahu 0 až 40 dB, pracujícího v pásmu 1 až 2 500 MHz. Navržený atenuátor je řízen mikrokontrolérem, který ovládá obvod integrovaného atenuátoru. Součástí atenuátoru je základní uživatelské rozhraní. Pro atenuátor byla navržena a posléze vyrobena DPS. Zařízení bylo následně sestaveno a změřeny jeho klíčové parametry.

This thesis deals with the design of a programmable attenuator with digital control. The main objective of the work is to design and create an attenuator with a nominal impedance of 50 , providing adjustable attenuation in the range of 0 to 40 dB, functioning within a bandwidth of 1 to 2 500 MHz. Control of the proposed attenuator is facilitated by a microcontroller that manages the settings of an integrated circuit attenuator. Furthermore, the attenuator features a basic user interface. A PCB was designed for the attenuator and subsequently manufactured. The device was then assembled and its key parameters were measured.
Programmable attenuator for laboratory measurement
Keywords: atenuátor; mikrokontrolér; útlumový článek; AVR; I2C; rotační enkodér; relé; DPS; VF; attenuator; microcontroller; attenuation pad; AVR; I2C; rotary encoder; relay; PCB; RF